Parts : A Novel - Flores, Shoney, 1985- (Book collections on Project MUSE., 2017)
"Parts tells the story of an auto parts store stocker and delivery driver who escapes into the written word to contrast the pelado environment inside the walls of the warehouse. Set in South Texas, where Mexico is a ten-minute drive, the novel deals with vulgar Mexican men working in the auto parts retail industry, men who create an atmosphere of machismo, immorality and sexual innuendo"--Publisher.